2021
DOI: 10.5194/amt-14-2359-2021
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic infrared gas analysis from longleaf pine fuel beds burned in a wind tunnel: observation of phenol in pyrolysis and combustion phases

Abstract: Abstract. Pyrolysis is the first step in a series of chemical and physical processes that produce flammable organic gases from wildland fuels that can result in a wildland fire. We report results using a new time-resolved Fourier transform infrared (FTIR) method that correlates the measured FTIR spectrum with an infrared thermal image sequence, enabling the identification and quantification of gases within different phases of the fire process. The flame from burning fuel beds composed of pine needles (Pinus pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…Canisters were used as a necessary safety precaution since the field fires were much less controlled than the wind tunnel burns and the FTIR setup precluded field use. Use of real-time measurement by FTIR provided other benefits (Banach et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Canisters were used as a necessary safety precaution since the field fires were much less controlled than the wind tunnel burns and the FTIR setup precluded field use. Use of real-time measurement by FTIR provided other benefits (Banach et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The flaming combustion samples are not included in this analysis. For the FTIR samples, two approaches were used (Scharko et al 2019a;Banach et al 2021). In the wind tunnel, a fixed stainless-steel probe located in the vicinity of the sample tube array captured gases emitted by the pyrolysing plant and pine needle fuels prior to the arrival of any combustion gases or the flame front.…”
Section: Wind Tunnel Firesmentioning
confidence: 99%
“…Two different sampling modes (dynamic -continuous gas flow through the White cell; static -gas flow into the White cell for a fixed time which was then valved shut) were used. Only the static samples (Banach et al 2021) were used in the present analysis. Analysis of the dynamic samples is currently incomplete and will be the focus of a future analysis.…”
Section: Wind Tunnel Firesmentioning
confidence: 99%
“…Seven burn units, designated as 16D1, 16D5, 16D6, 24A Main, 24A Triangle, 24B Main, and 24B Triangle, were selected due to having a significant sparkleberry component in their understory vegetation (Figure 2). Areas with significant sparkleberry coverage were preferred due to interest in the pyrolysis gases produced from burning sparkleberry during its growing season [17,23,28]. Each unit was approximately 0.16 hectares in area; the units were delimited by fresh bulldozer tracks, which served both as visible boundaries around each unit and also as firebreaks to prevent the spread of fire outside the units.…”
Section: Study Areamentioning
confidence: 99%
“…Sparkleberry, a deciduous shrub, can have a significant impact on the fire behavior that occurs in these forests by increasing the flame lengths when it ignites, resulting in greater heat release, spread rates, and potential damage to the overstory. While two previous studies [23,28] have indicated that certain gases such as phenol may be a characteristic gas of such berry plants upon pyrolysis (sparkleberry is a member of the Vaccinium genus), there are few other reports toward this end. While sparkleberry foliage obviously does not burn during the dormant season (no leaves), it does burn in the early growing season, i.e., after leaf-out.…”
Section: Introductionmentioning
confidence: 97%